Defining the role of gut microbiota‐derived ketamine metabolites in Alzheimer's disease: Nonhuman/Target identification and validation studies: Inflammation and innate immunity. (7th December 2020) - Pasinetti, Giulio Maria; Naughton, Sean X.; Trageser, Kyle J.; Harary, Joyce M.; Westfall, Susan
Abstract: Background: Ketamine, typically used for providing pain relief and sedation prior to surgical procedures, has recently been recognized as a potential therapy for disorders rooted in neuroinflammation such as major depression. Ketamine undergoes extensive metabolism and characterizing these metabolites is essential to understand the therapeutic efficacy and long‐term effects of ketamine treatment for neuroinflammation. Further, specific enantiomers of ketamine have been shown to specifically alter the composition of the gut microbiota, which through gut‐brain‐axis mechanisms, may contribute to its anti‐inflammatory activity. The objective of this study is to characterize the impact of the gut microbiota on ketamine metabolism and using these metabolites understand how ketamine can be used as a therapeutic for neuroinflammation associated with Alzheimer's disease (AD). Method: Using an in vitro model of the human gastrointestinal tract, EBIOME we are exploring the impact of ketamine on the human microbiome with metagenomic quantification of gut microbiome species and quantification of ketamine metabolites with UPLC‐MS/MS technology platforms. Ketamine is known to undergo extensive metabolism by liver P450 enzymes, which will interact with the gut microbiome derived metabolites. Hence, following validation in vitro, in ongoing studies ketamine will be chronically dosed into wildtype mice to understand how the gut microbiota‐derived metabolites affect the known liver‐derived secondary metabolites including norketamine and its hydroxylated isomers and dehydrogenated forms. Result: We have evidence in rodents, that ketamine amplifies Lactobacillus, Turicibacter and Sarcina spp. while reducing populations of the opportunistic pathogens Mucispirillim and Ruminococcus indicating that there is a species‐dependent metabolism of ketamine. Bioavailability and acute over chronic pharmacokinetics of these metabolites will be determined in the gut, blood and brain to understand how the gut‐liver metabolic interactions affect chronic ketamine dosing towards understanding the long‐term safety of ketamine. Conclusion: With an understanding of ketamine metabolism, ketamine chronically dosed into 5xFAD AD mouse models we will understand the brain‐bioavailable ketamine metabolites on neuroinflammatory pathophysiologies of AD. Ultimately these studies will help to asses microglia inflammatory activation and Alzheimer' disease neuropathology.